Continuous flow laser-induced unzipping of multiwalled carbon nanotubes - Thaar M. D. Alharbi (Journal of Taibah University for Science, 2024)
Unzipped multiwalled carbon nanotubes (MWCNTs) provide a route to graphene carbon ribbons (GNRs), which have application in electronic devices. Pulsed irradiation using an Nd:YAG laser operating at 1064 nm mediates such unzipping of MWCNTs dispersed in ethanol under shear stress within the vortex fluidic device (VFD). The method is scalable with the thin film device operating under continuous flow, while also avoiding the use of harsh chemicals and auxiliary substances. Unzipped MWCNTs are formed in 90% yield and have been characterized using scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, thermogravimetric analysis, X-ray powder diffraction and X-ray photoelectron spectroscopy. The systematically derived optimal laser power for unzipping was 250 mJ and increasing the laser power results in the fragmentation of the MWCNTs.